Theoretical treatment of a self-sustained, ball milling induced, mechanochemical reaction in the Fe2O3/Al system - Cuadrado Laborde, Christian Ariel (2003)
A theoretical approach to self-sustained reactions (SSR) is established based on self-propagating high temperature synthesis. The corresponding heat conduction equation has been solved numerically and conclusions about the occurrence of the reaction through the whole sample have been obtained from the relationship between the dissipation mechanisms. These results strongly suggest that radiation heat flux plays a dominant role in the propagation of the reaction in reactive ball milling processes. The influence of different parameters on the occurrence of the SSR or its development were studied. Data for the formation of iron-alumina composites by reducing hematite with aluminum were used, in order to obtain realistic values. However the results are sufficiently generic to extrapolate the conclusions to other high enthalpy reactions. © 2003 Elsevier Science B.V. All rights reserved.